Safety and Efficacy of Degradable Starch Microspheres Transcatheter Arterial Chemoembolization as a Bridging Therapy in Patients with Early Stage Hepatocellular Carcinoma and Child-Pugh Stage B Eligible for Liver Transplant - Roberto Minici; Michele Ammendola; Francesco Manti; Maria Anna Siciliano; Enrica Giglio; Marco Minici; Marica Melina; Giuseppe Currò; Domenico Laganà (Frontiers Media S.A., 2021)
In patients with early-stage hepatocellular carcinoma, awaiting liver transplantation, current guidelines by AASLD and ESMO recommend a bridging therapy with a loco-regional treatment to prevent progression outside transplantation criteria. The standard of care in delaying disease progression has been recognized to be the transarterial chemoembolization. Permanent occlusion of tumor feeding vessels has effects on tumour stromal microenvironment by inducing intra- and intercellular signaling processes counteracting hypoxia, such as the release of vascular endothelial growth factor, a promoter of neoangiogenesis, tumour proliferation and metastatic growth. Among chemoembolization interventions, TACE with degradable starch microspheres represents an alternative to conventional cTACE and DEB-TACE and it minimizes detrimental effects on tumour stromal microenvironment, guaranteeing a transient occlusion of tumour feeding arteries and avoiding VEGF overexpression.Between January 2015 and September 2020, 54 consecutive patients with early-stage hepatocellular carcinoma and Child-Pugh stage B, who had undergone DSM-TACE as a bridging therapy while awaiting liver transplantation, were eligible for the study. A total of 154 DSM-TACE was performed, with a mean number of 2.85 procedures per patient. 18 patients (33.3%) succeeded in achieving liver transplantation, with a mean waiting time-to-transplantation of 11.7 months. The cumulative rates of patients still active on the WL at 6 months were about 91 and 93% when considering overall drop-out and tumour-specific drop-out respectively. Overall survival was about 96% at 6 months and 92% at 12 months. 17 patients experienced adverse events after the chemoembolizations. For patients with HCC in the transplant waiting list and within the Child-Pugh B stage, life expectancy may be dominated by the liver dysfunction, rather than by the tumour progression itself. In this population subset, the choice of LRT is critical because LRT itself could become a dangerous tool that is likely to precipitate liver dysfunction to an extent that survival is shortened rather than prolonged. Hence, the current study demonstrates that DSM-TACE is not far from being an ideal LRT, because it has an excellent safety profile, maintaining an efficacy that guarantees a clear advantage on the dropout rate with respect to the non-operative strategy, thus justifying its use.